NLRP3 inflammasome and pyroptosis in cardiovascular diseases and exercise intervention - Ding, Ping; Song, Yuanming; Yang, Yang; Zeng, Cheng (Frontiers in Pharmacology, 2024)
NOD-like receptor protein 3 (NLRP3) inflammasome is an intracellular sensing protein complex that possesses NACHT, leucine-rich repeat, and pyrin domain, playing a crucial role in innate immunity. Activation of the NLRP3 inflammasome leads to the production of pro-inflammatory cellular contents, such as interleukin (IL)-1β and IL-18, and induction of inflammatory cell death known as pyroptosis, thereby amplifying or sustaining inflammation. While a balanced inflammatory response is beneficial for resolving damage and promoting tissue healing, excessive activation of the NLRP3 inflammasome and pyroptosis can have harmful effects. The involvement of the NLRP3 inflammasome has been observed in various cardiovascular diseases (CVD). Indeed, the NLRP3 inflammasome and its associated pyroptosis are closely linked to key cardiovascular risk factors including hyperlipidemia, diabetes, hypertension, obesity, and hyperhomocysteinemia. Exercise compared with medicine is a highly effective measure for both preventing and treating CVD. Interestingly, emerging evidence suggests that exercise improves CVD and inhibits the activity of NLRP3 inflammasome and pyroptosis. In this review, the activation mechanisms of the NLRP3 inflammasome and its pathogenic role in CVD are critically discussed.Importantly, the purpose is to emphasize the crucial role of exercise in managing CVD by suppressing NLRP3 inflammasome activity and proposes it as the foundation for developing novel treatment strategies.